La historia de un cuerpo silencioso (2014)
This overview highlights the importance of Criminal Investigation in the present paper aims to clarify the offense that caused the death of María Fernanda SOSA DIAZ, who is found by a farmer in a sack, in the village of Colombia, municipality of Colombia (Huila) who informs the police of, so it initiates the development of research, which will follow the procedures established standards for this type of crime that is contained in the Code of Criminal Procedure by Act 906 of 2004 and in conjunction with the process of investigation by the National police who are the ones who set the rules to be followed for this type of research, supported by a team of scientific and technical work of the knowledge acquired by the experts to identify, identify and then proceed prosecution of potential perpetrators, all through the aforementioned case